"Do it yourself moves and changes" PBXoIP system - Abd. Rahman, Farah Adibah (2006)
In this modern era, communication is an important element for organizations being it big organizations or small organizations. However, even though communication is crucial to business, telephony systems such as the PBX systems are expensive. IP PBX is another option for communication that is cheaper than the traditional PBX system, but the price is still high for small and medium enterprises to purchase. Most IP PBX solutions are hard to configure and maintained. Private Branch Exchange over Internet Protocol (PBXoIP) is a cost effective solution that does not only offer IP PBX communication, but also provide a user friendly web based management system that has been simplified for easy configuration. It is a “do it yourself moves and changes” PBXoIP system that helps organization to manage and control their PBXoIP. This feature is an advantage over other IP PBX solutions. PBXoIP is targeting to improve communication for small and medium enterprises for its cost effective and complete solution.